Dietary Approaches to the Management Of type 2 Diabetes (DIAMOND) in primary care: a protocol for a cluster randomised trial - Scragg, J; Morris, E; Wane, S; Noreik, M; Jerome, D; Yu, L-M; Galal, U; Dyson, P; Tan, GD; Fox, R; Breeze, P; Thomas, C; et al. (Elsevier, 2023)
Introduction: There is strong evidence that type 2 diabetes (T2D) remission can be achieved by adopting a low-energy diet achieved through total dietary replacement products. There is promising evidence that low-carbohydrate diets can achieve remission of T2D. The Dietary Approaches to the Management of type 2 Diabetes (DIAMOND) programme combines both approaches in a behaviourally informed low-energy, low-carbohydrate diet for people with T2D, delivered by nurses in primary care. This trial compares the effectiveness of the DIAMOND programme to usual care in inducing remission of T2D and in reducing risk of cardiovascular disease.